Detecting Areas Vulnerable to Sand Encroachment Using Remote Sensing and GIS Techniques; Case Study: Rigan, Fahraj and Narmashir Counties, Kerman Province - Ali Mehrabi (مخاطرات محیط طبیعی, 2020)
Sand dune advances pose a major threat to agricultural land, residential areas and residents of the eastern and southeastern parts of Kerman province. So that the occurrence of frequent sandstorms today is one of the most important environmental problems in these areas. The purpose of this research is to identify and potential the range of Rigan, Fahraj and Narmeshir cities in terms of Sand Encroachment. For this purpose, the sand dunes vulnerability index (SDEVI) was used. In this regard, five effective factors in the spread of sand, including wind intensity, soil moisture, topography, lithology type, and vegetation were used. After preparing the relevant maps, all of them were ranked in terms of impact on vulnerability and integrated into the GIS environment and the final vulnerability map was prepared. Accordingly, an area of 345 square kilometers is located in the area of high and very high vulnerability. The southern half of the city of Narmashir, 68 villages and parts of the communication network between the three Fahraj, Rigan and Narmeshir counties are in very high risk of Sand Encroachment. In order to verify the results of the SDEVI index, OLI sensor images related to Landsat 8 satellite and SENTINEL 1 radar images were used. By dividing the infrared band on the blue band, the sandy areas were identified and applying the correlation change technique (CCD) to radar images, the stability of sandy areas was determined. The results confirm the accuracy of the vulnerability index.